Strong contribution from sensible heat to global precipitation increase in climate models is not supported by observational based data - Myhre, Gunnar; Jouan, Caroline; Stjern, Camilla Weum; Hodnebrog, Øivind (Frontiers in Climate, 2024)
It has previously been shown that trends in sensible heat from climate models have had a substantial contribution to global precipitation changes. We illustrate that this is the case also in the most recent Coupled Model Intercomparison Project Phase 6 (CMIP6). However, we find that over the period since 1980 reanalyses do not support the reduction in sensible heat from the CMIP6 models and rather estimate a global increase in sensible heat which would contribute to a precipitation reduction. Satellite data over a period of two decades over global ocean generally show an opposite sign of the sensible heat trend to the CMIP6 models, similarly to the reanalyses.